The Role of Digital Coping in Strengthening Government Accounting Information Systems Based on E-Government - Nurul Izmi Muhajir; Wahyuni Wahyuni; Indriana Indriana (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims to examine the influence of digital coping on strengthening the e-government-based Government Accounting Information System (SIAP). The success of public sector digital transformation is not only determined by technology, but also the ability of officials to manage technostress through coping strategies. This quantitative study used Partial Least Square-based Structural Equation Modeling with respondents from several government agencies in Makassar City and South Sulawesi Province. The analysis results show that digital coping has a positive and significant effect on strengthening SIAP (t-statistics 11.126; p-value 0.000) and explains 61.6% of the variance. Effective coping strategies improve the accuracy, transparency, and accountability of government financial information management.